2018
DOI: 10.1159/000493320
|View full text |Cite
|
Sign up to set email alerts
|

A Rodent Model of Anxiety: The Effect of Perinatal Immune Challenges on Gastrointestinal Inflammation and Integrity

Abstract: Objectives: Gastrointestinal (GI) inflammation and GI integrity deficits are common comorbidities of neuropsychiatric disorders. Ongoing research suggests that these aberrations may be contributing to heightened immune signals that have the potential to disrupt neuronal homeostasis and exacerbate behavioural deficits. The current study aimed to determine whether the well-characterized animal model of neuropsychopathology, the maternal immune activation (MIA) model, produced GI inflammation and integrity disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…These findings may demonstrate an amelioration in microbiotic alterations by adulthood. As previous research suggests, a decrease in this bacteria could possibly account for the increased levels of circulating corticosterone and IL6 and CRHR1 mRNA found in the adolescent female MIA-ACE offspring in this study ( Cussotto et al., 2018 ; Hollins et al., 2018 ; Neuman et al., 2015 ).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…These findings may demonstrate an amelioration in microbiotic alterations by adulthood. As previous research suggests, a decrease in this bacteria could possibly account for the increased levels of circulating corticosterone and IL6 and CRHR1 mRNA found in the adolescent female MIA-ACE offspring in this study ( Cussotto et al., 2018 ; Hollins et al., 2018 ; Neuman et al., 2015 ).…”
Section: Discussionsupporting
confidence: 56%
“…In the hypothalamus, the neurotrophin brain-derived neurotrophic factor (BDNF) along with glucocorticoid signalling maintain CRH and glucocorticoid bioavailability ( Jeanneteau et al., 2012 ). Of particular interest, research has found that gut microbiota are involved in regulating the expression of BDNF ( Nemani et al., 2015 ), with alterations in both BDNF expression and gut microbiota found in patients with schizophrenia (reviewed in ( Hollins et al., 2018 )). Research shows that the bacteria B. longum can increase BDNF levels ( Alam et al., 2017 ), decrease circulating corticosterone levels, and reduce schizophrenia-like behaviour ( Orikasa et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2011) Rats Sprague Dawley M Post-weaning (P44) 0.5 IP 15–18 Serum 6 TNF-α Han et al. (2017) Mice ddY NR Post-weaning (P70) 5 IP 12–17 Hip, nucleus accumbens, CA1, CA3, dentate gyrus 5–6 C1q Hollins et al. (2018) Rats Wistar M Pre-weaning (P7)/Post-weaning (P84) 5 IV 10,19 Colon 6 IL-1β, IL-6, TNF-α Horváth et al.…”
Section: Resultsmentioning
confidence: 99%